Assessment of microfungi in fungus gardens free of the leaf-cutting ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Rodrigues, A. [UNESP]; Pagnocca, F. C. [UNESP]; Bueno, O. C. [UNESP]; Pfenning, L. H.; Bacci, M. [UNESP] (My University, 2005)
The purpose of this study was to determine the microfungi present in young nests of Atta sexdens rubropilosa when the fungus gardens were deprived of worker ants. The results were compared with another study in which worker ants had been killed by using toxic baits, and some species such as Acremonium kiliense, Escovopsis weberi, Moniliella suaveolens and Trichoderma sp. were confirmed among the most common inhabitants of this microenvironment, but differences in composition and proportion of species were observed. The importance and the role of these and other species of fungi within the symbiosis are discussed.
Keywords: Filamentous fungi; Leaf-cutting ant; Symbiosis; Acremonium (Ascomycota); Acremonium kiliense; Atta; Atta sexdens rubropilosa; Escovopsis weberi; Formicidae; Fungi; Hymenoptera; Moniliella suaveolens; Trichoderma